2018
DOI: 10.9767/bcrec.14.1.2549.42-50
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Ag3PO4 Photocatalyst with Varied Ammonia Concentration and Its Photocatalytic Activities For Dye Removal

Abstract: The highly active photocatalyst of Ag3PO4 could be synthesized under ammonia solution using the facile co-precipitation method with the starting material of AgNO3 and Na2HPO4.12H2O. The variation of ammonia concentration was designed at 0.00, 0.05, 0.15, and 0.30 M. The products were characterized using X-ray diffraction, UV-diffuse reflectance spectroscopy, and scanning electron microscopy. The photocatalytic activities were evaluated using the Rhodamine B degradation under blue light irradiation. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…[9] The authors believed that the reason for this was due to the different concentrations in the reaction solution affecting the nucleation and crystal growth during the sample preparation. Again using AgNO 3 and Na 2 HPO 4 , with no change in mass and molar ratio in different samples but with varying concentrations of ammonia added, Febiyanto [17] found that a concentration of 0.05 M ammonia was suitable for the synthesis of Ag 3 PO 4 with the highest photocatalytic activity; this was increased 4.13 times compared to Ag 3 PO 4 prepared without ammonia. This result was explained by the fact that the appropriate presence of ammonia successfully reduced the particle size and increased the homogeneity of the catalyst, in favor of the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] The authors believed that the reason for this was due to the different concentrations in the reaction solution affecting the nucleation and crystal growth during the sample preparation. Again using AgNO 3 and Na 2 HPO 4 , with no change in mass and molar ratio in different samples but with varying concentrations of ammonia added, Febiyanto [17] found that a concentration of 0.05 M ammonia was suitable for the synthesis of Ag 3 PO 4 with the highest photocatalytic activity; this was increased 4.13 times compared to Ag 3 PO 4 prepared without ammonia. This result was explained by the fact that the appropriate presence of ammonia successfully reduced the particle size and increased the homogeneity of the catalyst, in favor of the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…This has remained a challenge for researchers so far. Therefore, besides finding solutions to increase specific surface area, researchers also focus on enhancing the structural stability of the materials by adjusting the ratio of Ag + and PO 3− 4 [9,16,17] to find the most stable structure. In addition, increasing the lifetime of the electron/hole pair to increase the photocatalytic efficiency has always been of interest to research through the creation of a heterojunction between APO and other semiconductors [15,[18][19][20][21] as well as doping of APO with suitable ions.…”
Section: Introductionmentioning
confidence: 99%
“…Ag3PO4 photocatalysts may be synthesized by several methods. Coprecipitation [5,11], hydrothermal [8], sonochemical [12,13], and ultrasound-assisted synthesis [14] have been used to prepare this photocatalyst. Many researchers have designed the Ag3PO4-based composites to enhance the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…To decrease the environment pollutant in water containing dyes, there are some attempt such as electro-decolorization process (Amal, Febiyanto, Soleh, & Afif, 2016;Khosravi, Fazlzadehdavil, Barikbin, & Hossini, 2015), photocatalysis reaction (Febiyanto, Eliani, Riapanitra, & Sulaeman, 2016;Febiyanto et al, 2019), adsorption (Ikhsani, Santosa, & Rusdiarso, 2016;Subramani & Thinakaran, 2017), separation…”
Section: Introductionmentioning
confidence: 99%